2021
DOI: 10.1186/s10033-020-00495-7
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Morphology and Bonding Mechanism of Explosive Weld Joints

Abstract: Interfacial structure greatly affects the mechanical properties of laminated plates. However, the critical material properties that impact the interfacial morphology, appearance, and associated bonding mechanism of explosive welded plates are still unknown. In this paper, the same base plate (AZ31B alloy) and different flyer metals (aluminum alloy, copper, and stainless steel) were used to investigate interfacial morphology and structure. SEM and TEM results showed that typical sine wave, wave-like, and half-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The matrix has the basic function of protecting the reinforcement from the external environment, preventing the dispersed material (reinforcement) from coming into contact with acidic or corrosive media, as well as keeping the reinforcement in place and transferring tension to it [ 56 ]. The composite interface is a hypothetical surface without thickness that joins the reinforcement and the matrix by a certain adhesion mechanism, the interphase can be considered as the region resulting from the interaction between the reinforcement and the matrix with chemical and physical bonds ( Figure 1 ) [ 57 ]. One of the main challenges in processing composite materials is to obtain adequate interface and interphase between matrix and reinforcement.…”
Section: Interface Between Fiber-matrixmentioning
confidence: 99%
“…The matrix has the basic function of protecting the reinforcement from the external environment, preventing the dispersed material (reinforcement) from coming into contact with acidic or corrosive media, as well as keeping the reinforcement in place and transferring tension to it [ 56 ]. The composite interface is a hypothetical surface without thickness that joins the reinforcement and the matrix by a certain adhesion mechanism, the interphase can be considered as the region resulting from the interaction between the reinforcement and the matrix with chemical and physical bonds ( Figure 1 ) [ 57 ]. One of the main challenges in processing composite materials is to obtain adequate interface and interphase between matrix and reinforcement.…”
Section: Interface Between Fiber-matrixmentioning
confidence: 99%
“…Previous studies have found that collision produces molten metal flow, mixing and element diffusion, which is an important cause of the formation of molten blocks [5,10]. This high temperature and diffusion results in metallurgical bonding of the composite plate [12], at the same time, element diffusion is beneficial to the bonding strength of composite plates [11]. The super-cooling rate of the temperature plays an important role in the formation of the grains in the melted block [3], which causes the grains at the interface to deform, bend and deflect under the stress wave [5].…”
Section: Introductionmentioning
confidence: 99%
“…The molten metal cools and recrystallizes to form grains, and the formation of intermetallic compounds leads to the fining of grains Xue-jiao Li xjli@aust.edu.cn. [12]. Fronczek et al [15] found that aluminummatrix composites also had fine grain structure, grain refinement is more obvious near the titanium side.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations